Retrospective study of minimally invasive surgery verses open laminectomy or laminectomy with diskectomy - Madhavan, Girish K.; Mambally, Nikhil Pradeep (International Surgery Journal, 2021)
Background: Minimally invasive spine surgeries (MIS) are often considered superior to their open counterparts in view of smaller incisions, reduced blood loss, less post-operative pain and less hospital stay. In this study, we compared the clinical outcome of MIS and open procedure of lumbar laminectomy/discectomy. The objective of this study was to compare clinical outcome between the MIS and open procedure of lumbar laminectomy/discectomy. Methods: This was a retrospective study conducted at Government medical college, Kottayam, Kerala, India where we studied the patients who underwent MIS and open laminectomy/laminectomy with discectomy during the period January 2018 to January 2020. Results: We studied a total of 200 patients, among which 60% were males with a mean age of 50.58 years and 40% were females with a mean age of 53.59 years, 45.5% had L5 S1 IVDP, 30% had L4/5 IVDP, and 24.5% had L4/5 lumbar canal stenosis, 75.5% underwent laminectomy with discectomy and the rest (24.5%) underwent laminectomy with foraminotomy, 60% underwent open surgery and 40% underwent MIS. Conclusions: MIS was superior to its open analog in terms of intra operative blood loss as well as hospital stay. But open surgeries required less operation time, less C arm exposure, had better pain control and functional outcome and less recurrence in our study.